2014
DOI: 10.1111/mmi.12629
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the functional status of saeRS on in vivo phenotypes of Staphylococcus aureussarA mutants

Abstract: SUMMARY We investigated the in vivo relevance of the impact of sarA and saeRS on protease production using derivatives of the USA300 strain LAC. The results confirmed that mutation of saeRS or sarA reduces virulence in a bacteremia model to a comparable degree. However, while eliminating protease production restored virulence in the sarA mutant, it had little impact in the saeRS mutant. Additionally, constitutive activation of saeRS (saeRSC) enhanced the virulence of LAC and largely restored virulence in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 53 publications
8
45
0
Order By: Relevance
“…To date, the single most promising target that we have identified is the staphylococcal accessory regulator A (sarA), mutation of which limits S. aureus biofilm formation to a degree that can be correlated with increased antibiotic susceptibility and improved therapeutic outcomes in relevant animal models (18-23). We also confirmed that the increased production of extracellular proteases plays an important role in defining the biofilm-deficient phenotype of sarA mutants (14,16,17,23,24). Moreover, we demonstrated that sarA mutants exhibit reduced virulence in a murine bacteremia model and that this can also be correlated with the increased production of extracellular proteases owing to the decreased accumulation of specific virulence factors, including alpha toxin and phenol-soluble modulins (23,25).…”
supporting
confidence: 65%
See 2 more Smart Citations
“…To date, the single most promising target that we have identified is the staphylococcal accessory regulator A (sarA), mutation of which limits S. aureus biofilm formation to a degree that can be correlated with increased antibiotic susceptibility and improved therapeutic outcomes in relevant animal models (18-23). We also confirmed that the increased production of extracellular proteases plays an important role in defining the biofilm-deficient phenotype of sarA mutants (14,16,17,23,24). Moreover, we demonstrated that sarA mutants exhibit reduced virulence in a murine bacteremia model and that this can also be correlated with the increased production of extracellular proteases owing to the decreased accumulation of specific virulence factors, including alpha toxin and phenol-soluble modulins (23,25).…”
supporting
confidence: 65%
“…The protease-deficient derivative of LAC was unable to produce any extracellular protease other than the proteases encoded by the spl operon; the use of this protease-deficient strain was necessitated by the fact that the spl mutation is defined by resistance to erythromycin (14,16,19,23,25). However, previous studies confirmed that biofilm formation is comparable in LAC sarA mutants unable to produce any extracellular protease and those that retain the capacity to produce only the spl-encoded proteases (17,24).…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Considering the protective roles of the SaeRS TCS described above, it is not surprising that the SaeRS TCS is required for disease progression in several animal models of infection including silkworm and nematode killing [130,131], murine survival and skin infection [132], infective endocarditis [4], necrotizing pneumonia and skin infection [133], osteomyelitis [74], and sepsis [134]. The SaeRS TCS was even needed for staphylococcal gastrointestinal dissemination and transmission following bacteremia [135].…”
Section: The Role Of Sae In the Virulence Of S Aureusmentioning
confidence: 99%
“…111 The resulting changes in the profile of secreted virulence factors may lead to a reduced impact on tissue degradation or cell cytotoxicity. 40,112,113 Alternatively, it is possible that antibiotics initially reduce the bacterial burden, allowing bone healing to be initiated before the infection reactivates.…”
Section: What Is the Mechanism Of The Observed Pro-osteogenic Responsmentioning
confidence: 99%